Extracellular matrix molecules exhibit unique expression pattern in the climbing fiber-generating precerebellar nucleus, the inferior olive. (22nd January 2015) - Kecskes, S.; Gaál, B.; Rácz, É.; Birinyi, A.; Hunyadi, A.; Matesz, C.
Highlights: Extracellular matrix does not form perineuronal net in the inferior olive. Extracellular matrix appears in the neuropil and forms periaxonal coats in the inferior olive. Functionally different subnuclei of inferior olive exhibit different molecular composition of extracellular matrix. Abstract: Extracellular matrix (ECM) accumulates around different neuronal compartments of the central nervous system (CNS) or appears in diffuse reticular form throughout the neuropil. In the adult CNS, the perineuronal net (PNN) surrounds the perikarya and dendrites of various neuron types, whereas the axonal coats are aggregations of ECM around the individual synapses, and the nodal ECM is localized at the nodes of Ranvier. Previous studies in our laboratory demonstrated on rats that the heterogeneous distribution and molecular composition of ECM is associated with the variable cytoarchitecture and hodological organization of the vestibular nuclei and may also be related to their specific functions in gaze and posture control as well as in the compensatory mechanisms following vestibular lesion. Here, we investigated the ECM expression pattern in the climbing fiber-generating inferior olive (IO), which is functionally related to the vestibular nuclei. By using histochemical and immunohistochemical methods, the most characteristic finding was the lack of PNNs, presumably due to the absence of synapses on the perikarya and proximal dendrites of IO neurons. On the other hand, the darkly stained dots or ring-like structures in the neuropil might represent the periaxonal coats around the axon terminals of olivary synaptic glomeruli. We have observed positive ECM reaction for the hyaluronan, tenascin-R, hyaluronan and proteoglycan link protein 1 (HAPLN1) and various chondroitin sulfate proteoglycans. The staining intensity and distribution of ECM molecules revealed a number of differences between the functionally different subnuclei of IO. We hypothesized that the different molecular composition and intensity differences of ECM reaction is associated with different control mechanisms of gaze and posture control executed by the visuomotor-vestibular, somatosensory and integrative subnuclei of the IO.